2014
DOI: 10.15662/ijareeie.2014.0308038
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Voltage Sag and Swell Using Distributed Power Flow Controller

Abstract: ABSTRACT:Modern power utilities have to respond to a number of challenges such as growth of electricity demand especially in non-linear loads in power grids; consequently,That higher power quality should be considered. In this paper, DPFC which is similar to unified power flow controller (UPFC) in structure, which is used to mitigate the voltage sag and swell as a power quality issue. Unlike UPFC, the common dc-link in DPFC, between the shunt and series converter devices should be eliminated and three-phase se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(8 reference statements)
0
0
0
Order By: Relevance
“…Several paper or research work on voltage reduction has been reported in distribution systems [40,41]. The voltage sag in loop power distribution systems has been evaluated and analyzed by installing a superconducting fault current limiter [42], and the results are compared in two radial and loop power distribution systems.…”
Section: Summary Of Voltage Sagmentioning
confidence: 99%
“…Several paper or research work on voltage reduction has been reported in distribution systems [40,41]. The voltage sag in loop power distribution systems has been evaluated and analyzed by installing a superconducting fault current limiter [42], and the results are compared in two radial and loop power distribution systems.…”
Section: Summary Of Voltage Sagmentioning
confidence: 99%